AGAMA KATOLIK DI KOTA JAMBI 1925 – 2013 - Siti Heidi Karmela, Eva Meliana Magdalena Panggaribuan, (Universitas Batanghari Jambi, 2020)
AbstractThis research is a historical research with the theme of religion which examines religion from an empirical point of view rather than from a normative point of view. As for what is being researched is about the growth and development of Catholicism in the city of Jambi. Therefore, the purpose of this research is to explain historically the dynamics of Catholicism in Jambi City from the initial process of its spread to its development since the Dutch colonial period, the Japanese occupation, to independence, and to describe the existence of missionary groups who were important figures in the process of its spread. The method used is the historical method starting from the heuristic, criticism, interpretation, and historiographic stages. Some of the theories used refer to the theory from E.B. Taylor on the